Total Cerebral Small Vessel Score Association With Hoehn and Yahr Stage in Parkinson’s Disease - Ma, Xinxin; Li, Shuhua; Li, Chunmei; Wang, Rui; Chen, Min; Chen, Haibo; Su, Wen (Frontiers in Aging Neuroscience, 2021)
Background: This study aimed to evaluate the total cerebral small vessel disease (CSVD) score in patients with Parkinson’s disease (PD) at different stages and related factors. Methods: A 100 and seven patients with idiopathic PD and 62 normal controls (NCs) who underwent brain magnetic resonance imaging (MRI) were enrolled. PD patients were divided into two groups: early PD [(Hoehn and Yahr (H&Y) 1–1.5, n = 36)] and advanced PD (H&Y 2–4, n = 71) groups. We calculated the total CSVD score for each participant based on lacunes, high-grade white matter hyperintensities (WMH), enlarged perivascular spaces (EPVS), and cerebral microbleeds (CMBs). Differences in total CSVD score between the PD and NCs and between the two subgroups were compared. In addition, a multivariate logistic regression analysis was conducted to investigate the association between CSVD markers and clinical variables in PD. Results: Lacunes were found in 9.3% of patients with PD, periventricular WMH (PVWMH) in 89.7%, deep WMH (DWMH) in 81.3%, EPVS in 85%, and CMBs in 2.8%. Compared with NCs, patients with PD showed higher PVWMH and DWMH scores. Advanced PD patients exhibited greater PVWMH (P = 0.041), DWMH (P = 0.046), and total CSVD score (P = 0.044) than the early PD group. After adjusting for multiple variables, higher H&Y stage was independently correlated with increased total CSVD score (OR = 2.667, 95% CI 1.154–2.266) and PVWMH score (OR = 2.237, 95% CI 1.084–1.696). Conclusions: CSVD may play a critical role in patients with PD. The total CSVD score is a potential neuroimaging marker for monitoring the progression of PD.